6 X square + 1 X - 1
Attachments:
![](https://hi-static.z-dn.net/files/dc4/4a8c8222d44cd46e18667fb7c562c9c5.jpg)
Answers
Answered by
0
Hey
Here is your answer,
6x^2 + x - 1 = 0
6x^2 + 3x - 2x - 1 = 0
3x ( 2x + 1 ) - 1 (2x + 1 ) = 0
(2x+1)(3x -1)=0
2x+1 = 0
X = -1/2
3x -1 = 0
X = 1/3
Hope it helps you!
Answered by
0
Heya !!
6X² + X - 1
6X² + 3X - 2X - 1
3X ( 2X + 1 ) - 1 ( 2X + 1 )
(2X + 1 ) ( 3X - 1 ) = 0
X = -1/2 or X = 1/3
6X² + X - 1
6X² + 3X - 2X - 1
3X ( 2X + 1 ) - 1 ( 2X + 1 )
(2X + 1 ) ( 3X - 1 ) = 0
X = -1/2 or X = 1/3
Similar questions